Validity Of QR-Code-Based Science E-Modules Teaching Materials To Improve Literacy Ability Science - inezty salsabilla adi; I Ketut Mahardika; Diah Wahyuni (Universitas Negeri Padang, 2023)
This study aims to examine the validity of the QR-Code-based E-module to improve the scientific literacy skills of grade VIII junior high school students. Through QR-Code-based E-modules students can improve scientific literacy ability that need to be built. This research is quantitative research using the ADDIE model but in this development research it is carried out up to the validation stage. The validity test in this study was carried out by experts or validators who were experts in their field and consisted of three validators. The validation was carried out based on material and media validation. This research was conducted in class VIII-A in the 2022/2023 academic year with a total of 23 students. The results showed that the QR-Code based E-module teaching materials met the validity criteria with an average percentage of 84.97% for material validity and an average percentage of 87.03% for media validity with valid criteria. This research can be useful in improving scientific literacy ability in eighth grade junior high school students.